Quantitative analysis and partial characterization of cytotoxin production by Salmonella strains. - Ashkenazi, S (1988)
The pathogenesis of the wide-spectrum human disease caused by Salmonella species is poorly understood. Cytotoxin production by other enteric pathogens has been increasingly investigated recently, and data are accumulating regarding the role of cytotoxins in enteric infections and hemolytic uremic syndrome. We studied the cytotoxic activity of 131 Salmonella strains of the major serotypes, including 94 strains of Salmonella enteritidis, 12 strains of Salmonella typhi, and 25 strains of Salmonella choleraesuis. Cytotoxicity was quantitatively determined in sonic extracts by a [3H]thymidine-labeled HeLa cell assay. All Salmonella strains examined showed some degree of cytotoxic activity. The geometric means +/- standard deviations of the amounts of cytotoxin produced (50% cytotoxic dose per milligram of bacterial protein) were 27 +/- 2 for S. typhi, 65 +/- 2 for S. enteritidis, and 117 +/- 2 for S. choleraesuis. Analysis of variance showed that the differences in cytotoxin production by the three species were significant (P less than 0.001). No significant differences were found between stool isolates and invasive strains of the same species. Neutralization studies showed that the cytotoxins produced by all Salmonella strains were immunologically distinct from Shiga toxin and the closely related Shiga-like toxins produced by Escherichia coli. DNA hybridization studies with DNA probes for Shiga-like toxins of types I and II showed no hybridization. In each species the cytotoxin was heat labile and sensitive to trypsin treatment, which indicated that its active component was probably protein in nature. Upon ultrafiltration with Amicon membranes and gel filtration chromatography, cytotoxic activity was found in the molecular weight range of 56,000 to 78,000. Our findings indicate that salmonellae produce cytotoxin(s) that may play a role in the manifestations of the various species.